A Mobile Application to Reduce Time to Calculate Medication Dosage and Medication Administration Errors in Simulated Pediatric and Neonatal Settings: A Research Protocol for a Cross‐Over, Randomized Controlled Trial - Somaye Norouzi; Zahra Sarkohi; Leila Alizadeh; Leila Ahmadian (Health Science Reports)
ABSTRACT Background Pediatric and neonate medication safety is a major issue. Children are at a higher risk of adverse drug events and medication errors than adults. As the mediation administration is the final stage of protection to impede potential unintentional adverse effects on patients. Thus, there is a strong need for research to explore new ways of reducing medication administration errors and time to calculate medication dosage in the pediatric and neonatal context. The objective is to assess the effectiveness of the Medication Administration Clinical Decision Support Systems (MACDSS) compared to the traditional method in a simulated environment for pediatric and neonatal care. Methods An open‐label (unmasked), two‐treatment, two‐period, cross‐over randomized controlled trial will be conducted in pediatric and neonatal settings with simulated scenarios to assess time to calculate medication dosage and medication administration errors with the MACDSS application compared to the traditional method. This study will recruit 16 participants randomly (1:1) from the Afzali‐poor hospital in Kerman. The participants are supposed to perform nine highly realistic scenarios, three at a high level of complexity, three at a medium level, and three simple scenarios. For the cross‐over stage, different scenarios at the same level of complexity will be presented. The main outcome will be the time spent to calculate the drug dosage by the nurse. Conclusion Developing a MACDSS as a mobile application may significantly improve the time needed to calculate dosage or amount and lower medication administration errors. If this application proves to be effective, it can be a very cost‐effective means of improving outcomes in the medication administration process, positively affecting many pediatrics and neonates' patients. Trial Registration Irct.behdasht.gov.ir, ID: IRCT20240409061457N1 registered on June 22, 2024.